Domestic violence and the Islamic tradition - Chaudhry, Ayesha S. (Oxford : Oxford University Press, 2014)
A frank, personal investigation into the contentious issue of marital violence within Islamic law. Drawing heavily on the author's own experience, the book explores the attempt to reconcile a tradition of patriarchal authority with egalitarian values. The book presents an insightful and provocative contribution to the debate about women in Islam.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on January 6, 2014).
Keywords: Family violence (Islamic law); Women (Islamic law); Qur'an -- Evidences, authority, etc; Islamic ethics